A Polish Bra Obsessed Women Community as a Discours Community - Senderska, Joanna (Respectus Philologicus, 2015)
The article addresses a female virtual community consisting of enthusiasts of bra fitting and connoisseurs of beautiful, especially well-chosen, lingerie, mainly bras. The members of this community sometimes are called in Polish “stanikomaniaczki” (which can be translated into bra maniacs, bra obsessed women) or lobbystki (which means lobbyists). The aim of this article is to consider whether the bra obsessed women community meets the criteria for a discourse community proposed by John Swales (among others in his book entitled Genre Analysis: English in Academic and Research Settings, published in 1990). According to J. Swales, a community is a discourse community if its members: 1. have common goals; 2. use the specific mechanisms and means of internal communication; 3. use these mechanisms and means to obtain information or opinions and to share their knowledge or achievements with other members of the community; 4. communicate with each other using specific types of genres; 5. use a specific vocabulary; 6. have different levels of competence in transmitting and receiving messages, which gives individual members the status of "experts" or "novices". The author is also considering whether all online communities (using similar genres) focused on the exchange of information on a specific topic related to their interests that resulted in creating discourse communities.
Keywords: Discourse Community; Virtual Community; Online Community; Bra Obsessed Women; Lobbyists; Sociolect; Virtual Sociolect; Biuslang